2020
DOI: 10.3329/bjch.v44i1.49683
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Nebulized Magnesium Sulphate in the Treatment of Acute Bronchial Asthma Compared to Nebulized Salbutamol: A Randomized Control Trial

Abstract: Background: Nebulized salbutamol is commonly used in treatment of asthma in children. The use of nebulized MgSO4 is one of the different treatment options available during acute exacerbation. Objective: To compare the efficacy of nebulized MgSO4 with nebulized salbutamol in the treatment of acute asthma in children. Materials and method: This randomized controlled study was conducted in Dhaka Medical College Hospital between January to December 2016. Children of 7-12 years with acute exacerbation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“… 8 Studies indicated that nebulized MgSO 4 is not significantly associated with improved respiratory function or hospital admission, further need of treatment and it is equally effective as nebulized salbutamol for managing severe acute asthma in children. 1 , 2 , 9 The use of MgSO 4 is resulted in improved hospitalization and decreased the need of further treatment among children with severe acute asthma. Intravenous magnesium sulfate is the most effective therapy for children with significant impact on pulmonary function.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Studies indicated that nebulized MgSO 4 is not significantly associated with improved respiratory function or hospital admission, further need of treatment and it is equally effective as nebulized salbutamol for managing severe acute asthma in children. 1 , 2 , 9 The use of MgSO 4 is resulted in improved hospitalization and decreased the need of further treatment among children with severe acute asthma. Intravenous magnesium sulfate is the most effective therapy for children with significant impact on pulmonary function.…”
Section: Introductionmentioning
confidence: 99%
“…3 The standard treatment of acute severe asthma includes oxygen inhalation, nebulization with salbutamol and ipratropium along with intravenous steroids. 4 Additional therapies include subcutaneous or inhaled epinephrine/adrenaline, intravenous (IV) or inhaled magnesium sulfate (MgSO4) and IV aminophylline. 5 According to GINA (Global Initiative for Asthma) / BTS (British Thoracic Society) guidelines, usage of intravenous and nebulized magnesium sulphate can also be useful in the management of asthma 6 .…”
Section: Introductionmentioning
confidence: 99%